Making Waves for Nigerian Youths Through Education and Technology: The Harsh Fantasy of the Environment - Isiaka Adeniran Akinyemi; Kabiru Olusegun Akinyemi (Journal of Educational Sciences, 2023)
The goal of this paper is to bring to light an adequate understanding of the concepts of "making waves," to capture the minds of parents, students, and other members of society, on how education and technology can help to excel, and to educate one on the negative effects of social vices on the environment. However, the benefits of education and technology to both individuals and society were examined as a catalyst for social and economic sustainability. Hence, education and technology have been unraveled as a medium for achieving sustainable development when youths strive for excellence in their academic pursuits and eschew vices. The paper looked at technology and its emergence in the twenty-first century, how to make waves through digitalisation, the importance of digital education in Nigerian schools, challenges to the digitalisation of education in Nigeria, and ways to strive for excellence. This paper suggested, among others, that government should sufficiently fund education from the primary to the high school levels. Drugs, sex abuse, cults, and other vices must be rejected by every member of the community. A decrease in the number of children who are not in school must also be ensured by the government at all levels of the nation, along with provisions for the necessary infrastructure, learning, and teaching tools.